Pathogenesis, Mechanism and Modern Clinical Diagnosis of Placenta Accreta in the Uterine Wall - Vladimirovna, Sarkisova Viktoriya (American Journal of Bioscience and Clinical Integrity, 2025)
The case report of successful conservative treatment of 2 patients with true placenta accreta is presented. Both patients had placenta previa and a cesarean scar on the uterus. Placenta accreta was diagnosed during pregnancy using ultrasound and magnetic resonance imaging. Given the diagnosis, a decision was made to perform a lower cesarean section with subsequent embolization of the uterine arteries. The placenta remained in place. In the postoperative period, delayed repeated embolization of the uterine arteries was performed. After partial expulsion of the placenta, the remaining placental tissue was removed by curettage and hysteroscopy. During dynamic follow-up, the patients experienced complete restoration of menstrual function.